Revitalization of necrotic mature permanent incisors with apical periodontitis: a case report - Emre Nagas; M. Ozgur Uyanik; Zafer C. Cehreli (Restorative Dentistry & Endodontics)
Despite considerable focus on the regenerative endodontic treatment of immature teeth with necrotic infected pulps and apical periodontitis, little data exist with regard to its possible implementation in necrotic permanent teeth with complete apical and radicular development. The present report describes the procedures and outcome of a regenerative endodontic treatment approach in 2 previously-traumatized incisors with closed apex with apical periodontitis. A 2-visit treatment procedure was employed. At initial visit, the root canals were copiously irrigated, followed by placement of a triple antibiotic paste containing ciprofloxacin, metronidazole, and clindamycin into the root canals. After 4 weeks, the antibiotic paste was removed, and apical bleeding was initiated with size 10 hand files beyond the apices. The root canals were coronally sealed with mineral trioxide aggregate, and the access cavities were restored with bonded resin composite. At post-operative 60 months, both teeth were remained asymptomatic, with the recall radiographs showing complete resolution of apical radiolucency and reestablishment of periradicular tissues. In both teeth, the dimensions of root space remained unchanged as verified by image analysis. The revitalization protocol utilizing root canal disinfection and induced apical bleeding in necrotic, closed-apex incisors may offer a clinically acceptable alternative to conventional root canal treatment.